Relasi Kendaraan Tempur Tank dan Lapis Baja Rusia dalam Operasi Perang Darat di Ukraina - Prihantoro, Mitro (PT Hakhara Akademia Indonesia, 2024)
Russia’s invasion of neighboring Ukraine in February 2022 began by using Russian ground troops to breach the border from various directions. Russia mobilized all its military strength to attack Ukraine, including the use of tanks and armored vehicles. Initially, Russian troops benefited from the attacks launched, however, the Russian troops' attacks gradually became ineffective due to the resistance applied by Ukraine. Many images show Russian tanks and armored vehicles suffering damage and destruction. This research aims to explain and analyze the deployment of Russian tanks and armored fighting vehicles in ground combat operations in Ukraine. The research method is qualitative with a literature study approach and explaining the focus of the research is carried out descriptively. The results of research describing the war in Ukraine do not reveal anything fundamentally new about tanks. Russian tanks and armored vehicles were damaged and destroyed due to gathering in the open without camouflage and inadequate logistical planning, in addition to that Russian tanks were not operated properly. Ukrainian troops’ use of anti-tank guns and missiles was so effective that Russian tanks had difficulty advancing. The reflection of Russian tanks and armored fighting vehicles in the beginning of land operations in Ukraine exposed the weaknesses of Russian tank designs, logistical vulnerabilities and the effectiveness of modern anti-tank weapons.